Qualitative Phytochemical Screening of Ethanolic Extract of Centella asiatica L. Leaves - Rizky Hasyara Putri; Rahmawati Rahmawati; Mukarlina Mukarlina (Jurnal Biologi Tropis, 2026)
Indonesia is a tropical country with high plant biodiversity, including Centella asiatica L., a medicinal plant known to contain various bioactive secondary metabolites. This study aimed to identify the classes of secondary metabolites present in the ethanolic leaf extract of C. asiatica through qualitative phytochemical screening. The research was conducted as a laboratory-based study using standard phytochemical methods based on classical procedures to detect alkaloids, flavonoids, tannins, saponins, and steroids. The results showed that the ethanolic extract of C. asiatica leaves contained all tested secondary metabolite groups, indicating a diverse phytochemical profile. The presence of these compounds suggests potential biological and pharmacological activities, such as antimicrobial and antioxidant properties. Further studies are recommended to isolate and characterize individual bioactive compounds and to evaluate their specific biological activities.